The Effect Of Work Motivation And Work Discipline on Employee Performance in the West Cikarang Sub-District Office - Dadang Heri Kusumah; Rismawati Rismawati (Enrichment : Journal of Management, 2022)
The purpose of this study was to determine the effect of work discipline on west Cikarang sub-district employees and work motivation on West Cikarang sub-district employees. The scope of this study is to test the influence of work discipline and work motivation on employees of the West Cikarang sub-district. Data collection techniques include observation, dissemination of questionnaires and literature studies. The type of research used is with a quantitative approach. The analytical methods to be used are validity test, reliability test, classical assumption test, multiple linear analysis and hypothesis test. Sampling in this study used a saturated sample technique. The results showed that work motivation had a negative effect not significantly on employee performance while work discipline had a positive and significant effect on the performance of employees in West Cikarang sub-district.